Stages and Directions of Development of the Digital Economy in Uzbekistan - Ergashevna , Saatova Lolakhon (Researchparks Publishing, 2023)
This article presents the stages of the formation of the digital economy in foreign countries and Uzbekistan, the analysis of the processes of the digital economy and its directions.